Comparison of Methods to Identify Stress Urinary Incontinence in Women With Pelvic Organ Prolapse. Issue 1 (January 2021) - Martin, Laura; Ossin, David; Schachar, Jeffrey; Devakumar, Hemikaa; Alas, Alexandriah; Davila, G. Willy; Reis, Isildinha M.; Miao, Feng; Hurtado, Eric
Abstract : Objective: The aim of the study was to compare which test is most sensitive in identifying stress urinary incontinence (SUI) in women with pelvic organ prolapse using urodynamics (UDS) as the criterion standard: cough stress test (CST) or pyridium pad test. Methods: This was a prospective study of women with pelvic organ prolapse stage II or greater who desired surgical management for prolapse. Each patient underwent preoperative urinary testing: UDS, CST, and a 24-hour pyridium pad test. Results: A total of 84 patients were analyzed. Using UDS as the criterion standard, both the CST and the pyridium pad test showed a fair agreement with UDS outcomes (κ = 0.27 for both tests). There was no statistically significant difference between the CST and pyridium pad test, with estimated sensitivities of 34.4% versus 60.6% ( P = 0.791) and specificities of 90.4% versus 84.6% ( P = 0.508). The pyridium pad test was found to have a statistically significant difference in identifying the subjective complaint of SUI (38.6%, P = 0.003) compared with other tests. Patients with occult incontinence were identified 42.5%, 17.5%, and 10% of the time during UDS, CST, and pyridium pad testing, respectively. Conclusion: Our data suggest that the sensitivities of the CST and pyridium pad test for stress incontinence and occult stress incontinence in patients with pelvic organ prolapse are low when compared with UDS as the criterion standard. Urodynamics has an important role in preoperative identification of occult SUI.